Informal Livelihoods and Governance in South Africa The Hustle - Jinnah, Zaheera (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book offers a compelling account of everyday life, livelihoods, and governance in post-apartheid South Africa among the urban poor and marginalized, anchored in and through a critique of the concept of informality, or living outside of the state, its laws, services, and protection. Using a case study of the Zama Zama, loosely translated from the isiZulu as 'to hustle, or to strive' and colloquially used to refer to those working as informal artisanal miners on Johannesburg's numerous disused and abandoned gold mines, the book documents an ethnography of this community's everyday lives, struggles, and hopes. It provides an intimate account of a community, its social relations, and its political relationship to the state. The narratives of the Zama Zama are used to raise broader questions about precarity, belonging, and governance in post-apartheid South Africa, and suggest that pervasive informality could risk the country's democratic order. Zaheera Jinnah is Assistant Professor in the School of Social Work, University of Victoria, Canada, and a research associate at the African Centre for Migration and Society, University of the Witwatersrand, South Africa. Her research, teaching and community work over the last 12 years centres on migration and African studies. She has published widely in the academic and popular press, including the co-edited book Gender and Mobility in Africa (with K. Hiralal, Palgrave Macmillan, 2018).